2008
DOI: 10.1093/intqhc/mzn039
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of primary care service quality in Afghanistan

Abstract: The government's strategy to form partnerships with non-governmental organizations has led to higher quality of care provided to the poor. This represents a promising start in the reconstruction of Afghanistan's health system and provides useful evidence to other countries striving to increase access to quality care for the poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…23 Similarly, in a study from Uganda, the quality index was 44% higher in facilities with at least one provider trained in IMCI, 24 a finding that further strengthens the case for greater investments in IMCI. We found that the proportion of providers ( Table 4, cont.)…”
Section: Discussionmentioning
confidence: 90%
“…23 Similarly, in a study from Uganda, the quality index was 44% higher in facilities with at least one provider trained in IMCI, 24 a finding that further strengthens the case for greater investments in IMCI. We found that the proportion of providers ( Table 4, cont.)…”
Section: Discussionmentioning
confidence: 90%
“…Recognition of these two services as best functioning services does not mean that they are working perfectly and do not suffer from shortcomings. Studies from Afghanistan and Nigeria have also reported a generally better satisfaction with maternal and child care services in PHCCs compared to other services [47,48]. There was also a general consensus about devoting inadequate time to patients at antenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, users from households with a head who had some education were less likely to be satisfied; perhaps they look for higher standards. A study based on data collected from primary health care facilities in Afghanistan in 2004 found that poorer service users got better quality of service in NGO-contracted facilities than directly managed government facilities [15]. …”
Section: Discussionmentioning
confidence: 99%